Carbon Coated ZnFe2O4 Nanoparticles for Advanced Lithium‐Ion Anodes. Issue 4 (2nd November 2012) - Bresser, Dominic; Paillard, Elie; Kloepsch, Richard; Krueger, Steffen; Fiedler, Martin; Schmitz, René; Baither, Dietmar; Winter, Martin; Passerini, Stefano
Abstract The preparation and electrochemical characterization of a new material consisting of carbon coated ZnFe2O4 nanoparticles is presented. This material, which offers an interesting combination of alloying and conversion mechanisms, is capable of hosting up to nine equivalents of lithium per unit formula, corresponding to an exceptional specific capacity, higher than 1000 mAh g−1. Composite electrodes of such a material, prepared using environmentally friendly sodium carboxymethyl cellulose as binder, showed the highest, ever reported, specific capacity and high rate performance upon long‐term testing. Furthermore, in situ X‐ray diffraction analysis allowed identifying the reduction process occurring upon initial lithiation.